Activation of mononuclear phagocytes and its relationship to asplenia and phosphatidylserine exposing red blood cells in hemoglobin E/β‐thalassemia patients - Banyatsuppasin, Wansa; Butthep, Punnee; Atichartakarn, Vichai; Thakkinstian, Ammarin; Archararit, Napaporn; Pattanapanyasat, Kovit; Chuncharunee, Suporn (American journal of hematology, 2011)
Aged or abnormal red blood cells with exposed phosphatidylserine (PSRBCs) are cleared from the circulation by splenic macrophages. In asplenic patients, other mononuclear phagocytic cells in tissues and in circulation may function in this capacity. To better understand these changes and the relationship among splenic status, PS-RBCs, blood monocytes, and serum tumor necrosis factor (TNF-α), a product of mononuclear phagocyte activation, patients with hemoglobin E/β-thalassemia (E/β-Thal) were studied. Whole blood of 20 nonsplenectomized, 20 splenectomized E/β-Thal patients, and 20 healthy subjects was assayed for PS-RBCs; for monocytes, activated monocytes, and monocyte response to lipopolysaccharide stimulation; and serum was assayed for TNF-α. Asplenic E/β-Thal patients had significantly increased (P < 0.05) amounts of PS-RBCs, monocytes, activated monocytes, and levels of serum TNF-α. The amount of PS-RBCs correlated with levels of serum TNF-α, but the amount of activated monocytes did not correlate with either the amount of PS-RBCs or levels of serum TNF-α. Monocyte response to lipopolysaccharide stimulation in asplenic patients was not as efficient as in the other patients or in normals (77 vs. 404, and 304 folds increment, respectively). The results suggest that splenectomy in E/β-Thal patients led to an increased amount of PSRBCs and activation in the mononuclear phagocytic system.